PERISTILAHAN DALAM BERLADANG PADI MASYARAKAT DAYAK SALAKO: KAJIAN SEMANTIK - Hermina, Hermina; Patriantoro, Patriantoro; Muzammil, A.R. (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract This research is focused on the semantic field of terminology in paddy farming of Dayak Salako community. Traditional paddy farming is about tools and processes. A common problem in this study 'How does the terminology of paddy farming in the Dayak Salako community in semantic studies?'. The general problem is confined to four subproblems. Those are form of terms, components of meanings, lexical meanings, and cultural meanings. This study aims to describe the form of term, components of meaning, cultural meaning, and meaning of lexical contained in paddy farming terminology of Dayak Salako community. Based on the analysis, it was found that in terms of farming rice Dayak Salako there are 31 data, those were divided into four stages, namely seven terminology: one pre-planting process, seven planting processes, three pasca-planting, 14 harvesting processes, five post-harvest processes, and there are 21 terminology tools, seven terminology place names, one post-harvesting time period, and six terminology. Lexical meaning contained in paddy farming terminology in Dayak Salako include terminology processes, tools, place names, post-harvesting time, and the results Keywords: Terminology, paddy farming, Semantics